Study on the distribution of airflow velocity within heat exchange pipes and heat saving performance of the underground heat storage system in greenhouse - WANG Yong-wei; LIANG Xi-feng; MIAO Xiang-wen; CUI Shao-rong (浙江大学学报. 农业与生命科学版)
According to the air and soil temperature requirement of crops at seedling stage, a new underground heat storage system to be used in greenhouse was designed. As a key factor of heat exchange, distribution of airflow velocity in the heat exchange pipes was measured. The results indicated that air flux was evenly distributed and the flowing air in every heat exchange pipe was in a turbulence state, thus enhancing heat convection between the air and pipe walls. It is also shown from theoretical analysis that the heat saved was more than the electric energy consumed in the system, and the effect of energy saving was significant.